Acute Gluteal Compartment Syndrome with Nonclassical Symptoms: A Case Report on an Easily Missed Diagnosis. Issue 2 (April 2021) - Davis, Benjamin J.; Mak, Ryan; Schneider, Andrew; Brown, Nicholas M.
Abstract : Case: A 34-year-old man presented to the emergency department with rhabdomyolysis, acute kidney injury, and pain in the gluteal region after falling asleep on his side after heroin and alcohol use. On examination, he had swollen gluteal compartment musculature; however, he tolerated full passive range of motion with minimal pain. Intercompartmental pressure measured >110 mm Hg; therefore, emergent fasciotomy of the gluteal compartment musculature was performed. Timely treatment of his acute compartment syndrome produced minimal functional deficits with a favorable outcome. Conclusion: Clinicians should be vigilant in the setting of patients with prolonged gluteal pressure, particularly with alcohol or drug use, to avoid potential serious complications of a missed acute compartment syndrome diagnosis and be aware that every case may not have all of the components of the classic presentation.